The effect of educational play tools on fine motor development in early childhood education - Nurul Kartika Putri; Delila Nur Hamidah (CV. SPDFHarmony, 2025)
Background: Fine motor development is a fundamental aspect of early childhood growth that supports children’s readiness for academic tasks, self-care, and independent learning. In early childhood classrooms, fine motor stimulation is closely related to the availability and effective use of educational play tools that encourage active manipulation and sensory–motor coordination. However, learning practices often rely on worksheet-based activities, resulting in limited opportunities for hands-on engagement. Aims: This study aims to examine the effect of educational play tools on the fine motor development of children aged 3–4 years in early childhood education settings. Method: This study employed a quantitative approach using a pre-experimental one-shot case study design. The participants were 17 children aged 3–4 years at Tresna Asih 3 Kindergarten in Bandar Lampung. The intervention involved structured learning activities using educational play tools, including finger painting, seed-based collage activities, origami manipulation, and patterned cutting tasks. Data were collected through observation instruments measuring fine motor indicators and analyzed using descriptive statistics and one-way analysis of variance. Results: The findings indicate that educational play tools have a statistically significant effect on children’s fine motor development. Among the implemented activities, origami and finger painting showed the strongest contributions to fine motor performance, while cutting activities required higher levels of coordination and readiness. Overall, children demonstrated improved finger control, hand–eye coordination, and fine motor precision following the intervention. Conclusion: Educational play tools are effective learning media for enhancing fine motor development in early childhood education. Structured play-based activities supported by appropriate teacher facilitation contribute meaningfully to children’s fine motor skill development.